Energy Efficiency Policies to Face Buildings’ Climate Change Effects in Paraguay - Fabiana Silvero; Fernanda Rodrigues; Sergio Montelpare (Applied Sciences, 2020)
Nowadays, the importance of implementing energy efficiency (EE) measures is growing significantly worldwide, based on its potential to reduce energy demands and mitigate climate change effects. Paraguay is a developing country with the highest per capita hydroelectric energy generation in the world, but only 18% of local consumption is hydroelectric and 41% of its energy matrix corresponds to oil products. This paper aims to analyse the importance the Country places on EE as a strategy towards sustainable development and to highlight as EE is an effective pathway to mitigate the climate changes and contrast their effects. The authors initially provide an insight into the climate scenarios for Paraguay and underline the effects of the climate changes on the buildings’ comfort. Subsequently, the authors provide, by resourcing a bibliographic review, a description of the Paraguayan sectors of greater energy consumption, its policies and targets set for increasing EE. Besides, the main EE projects developed by other neighbouring South American countries are analysed to show the level of development of each one in the scope of EE and to offer a reference basis of potential virtuous solutions to be adopted in Paraguay. A focus on the building sector is also made to provide a foundation for policy analyses to enhance EE in this sector. As a result of this review, evidence that EE is beginning to take part in Paraguay’s public policies was found, with the leaders becoming aware of its importance. Nevertheless, many concrete results could not be achieved as of yet and overcoming these barriers still involve a great challenge. Regarding the building sector, few advances have been noticed regarding the regulations of buildings’ thermal performance, a reason for which the National objectives set need to be more specific to achieve greater collective awareness to enforce them. Finally, key actions are recommended for Paraguay aiming to improve EE levels to face the climate change phenomenon.